Propiedades psicométricas del cuestionario de afronta¬miento al estrés para pacientes oncológicos (CAEPO) - Miaja Avila, Melina; Romero Retes, Rocío; Ibáñez Guerra, Elena; Soriano Pastor, José; García-Conde, Ana (Psicooncología, 2017)
The goals of the study are: 1) to analyze the factorial structure of the Coping to Stress Questionnaire for Oncologic Patients instrument by the use of a factorial exploratory and confirmatory analysis; 2) to estímate the internal reliability of the factors; 3) to describe the distribution of the factors; 4) to analyze the mean differences of the coping strategies between men and women. The Coping to Stress Questionnaire for Oncologic Patients (González, 2004) was used for 148 oncologic patients. It is given suggestions to reduce the questionnaire to 35 items, It was found four correlatonated factors estructure with internal reliability from adecuated to high. The factors distribution was adjusted to the normal curve and it was not found significative differences between men and women. In future investigation, it is suggested to use this questionnaire un clinic samples from Spain and othes spanishspeaking countries.